THE EFFECT OF SCARCITY MESSAGES AND NETWORK SIZE ON PURCHASE INTENTION OF SKINCARE PRODUCTS IN TIKTOK LIVE STREAMING - Maulyda, Shielfani Nur; Ahadi, Muhammad Nur (Jurnal Komunikasi & Media Digital, 2023)
This research aims to determine the effect of Message Scarcity and Network Size in Tiktok Shop @somethincofficial, on Somethinc purchase intention among Generation Z. According to iPrice (2020), Somethinc, Skintific, and The Originote on tiktok live streaming, @somethincofficial has a significant presence in the Gen Z market, however with Somethinc having a 13% penetration rate among 18-24 year olds, which this figure is smaller than @skintific_id and @TheOriginote. In this research employed quantitative methods with purposive sampling techniques. The resulut found that the scarcity message variable has an influence on purchase intention with a significance of 0.000. Furthermore, the network size variable has an influence on purchase intention with a significance value of 0.000. And the independent variables (X1) and (X2) have an influence of 40.6% on the dependent variable (Y).